Роль самоорганізації у процесі формування громадянського суспільства - Нечітайло, І. С.; Nechitailo, I. S.; ORCID: https://orcid.org/0000-0002-0656-0370; Борюшкіна, О. В.; Boriushkina, O. V. (Соціальні технології: актуальні проблеми теорії та практики. - 2021. - Вип. 92. - С. 95-102, 2021)
Розглянуто проблему формування громадянського суспільства в Україні. Мета статті полягає в соціологічній концептуалізації самоорганізації як умови формування громадянського суспільства. Самоорганізація розглядається як процес формування просторової, темпоральної та функціональної структур системи, що виникає спонтанно, проявляється стрибкоподібними переходами за певних характеристик системи та без цілеспрямованого впливу ззовні. Підкреслено, що інститути за характером їх формування поділяються на організовані та самоорганізовані. Громадянське суспільство представляється як таке, що утворюється та функціонує на основі самоорганізації його структур. Розкрито явище квазігромадянського суспільства, яке також ґрунтується на самоорганізаційних процесах. Підкреслено роль правових форм як таких, що виключають можливість негативних самоорганізованих інституцій.

The article is devoted to the problem of forming civil society in Ukraine. It is noted that the phenomenon of civil society is attracting more and more attention of modern sociologists and representatives of other sciences about man and society, although it is not sufficiently studied. It is emphasized that against the background of a variety of scientific and scientific-methodological publications about programs and recommendations for the development and promotion of civic activity (including youth), sociological research shows low civic activity and unformed civic consciousness of Ukrainians. In addition, the fragmentary scientific knowledge of civil society, the lack of a holistic scientific vision of this phenomenon, the blurring of the relationship between sociological, philosophical, pedagogical, legal and other approaches to its study. According to the authors, this situation requires a deeper understanding of the genesis of civil society. Thus, the purpose of the article is the sociological conceptualization of self-organization as a condition for the formation of civil society. Self-organization is considered as a process of formation of spatial, temporal and functional structures of the system, which arises spontaneously, is manifested by abrupt transitions with certain characteristics of the system and without purposeful influence from the outside. It is emphasized that the institutions by the nature of their formation are divided into organized and selforganized. Self-organized institutions arise spontaneously, functional connections in them are horizontal, management goals can change, the product and result of activities are probabilistic, not known in advance. Civil society is presented as one that is formed and functions on the basis of self-organization of its structures. The phenomenon of quasi-civil society, which is also based on self-organizational processes, is revealed. The role of legal forms as such, which exclude the possibility of negative self-organized institutions, is emphasized.

Рассмотрена проблема формирования гражданского общества в Украине. Цель статьи состоит в социологической концептуализации самоорганизации как условия формирования гражданского общества. Самоорганизация рассматривается как формирование пространственной, темпоральной и функциональной структур системы, которая возникает спонтанно, проявляется скачкообразными переходами при определенных характеристиках системы и без целенаправленного воздействия извне. Подчеркнуто, что институты по характеру их формирования делятся на организованные и самоорганизующиеся. Гражданское общество представляется как образующееся и функционирующее на основе самоорганизации его структур. Раскрыто явление квазигражданского общества, которое также основывается на самоорганизационных процессах. Подчеркнута роль правовых форм как исключающих возможность негативных самоорганизованных институтов.
The role of self-organization in the process of civil society formation
Нечітайло, І. С. Роль самоорганізації у процесі формування громадянського суспільства / І. С. Нечітайло, О. В. Борюшкіна // Соціальні технології: актуальні проблеми теорії та практики. - 2021. - Вип. 92. - С. 95-102. - DOI: https://doi.org/10.32840/2707-9147.2021.92.9.
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; соціологічні дослідження; sociological research; социологические исследования; громадянське суспільство; civil society; гражданское общество; демократія; democracy; демократия; інституціоналізація; institutionalization; институционализация; самоорганізація; self-organization; самоорганизация; соціальний порядок; social order; социальный порядок